MarPEM: An agent based model to explore the effects of policy instruments on the transition of the maritime fuel system away from HFO. (August 2017) - Bas, G.; De Boo, K.; Vaes-Van de Hulsbeek, A.M.; Nikolic, I.
Highlights: We assess effects of different policy instruments on the adoption of maritime LNG. We consider the effects on the entire maritime fuel system, not just a single vessel. LNG can only be adopted if it is globally available. Enforcement of emission regulations should aim to keep LNG more attractive than HFO. Stimulation of vessel refurbishment increases the speed of the transition. Abstract: To lower the emissions of deep sea shipping, policymakers aim to decrease the use of heavy fuel oil (HFO) as a maritime fuel. Multiple alternatives for HFO exist, but despite new regulations, their use is still limited. To stimulate shipping companies to replace HFO by one of the alternatives, policymakers can use a variety of policy instruments. In this paper, we present a comprehensive system perspective of the maritime fuel system and agent-based model (MarPEM) that can be used to study the effects of policy instruments on the transition away from HFO. In contrast to existing studies on reducing maritime emissions, our system perspective captures the relations and dynamics between different components of the maritime fuel system. Thereby, it can account for the feedback and non-linear dynamics in the system. We illustrate the use of MarPEM to assess the effect of three policy instruments that each influence the maritime fuel system differently. The outcomes of the experiments are in line with previous studies and the opinion of industrial experts. The model is thus a valid representation of the maritime fuel system. By presenting a sufficiently detailed representation of the marine fuel socio-technical system, listing clear and detailed assumptions, and publishing the source code, future studies can use this work as basis to study the effects of other policy instruments. Thereby, this research enables future detailed studies of the maritime fuel system's transition.